2023
DOI: 10.18502/jovr.v18i3.13774
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Values using Icare® Rebound Tonometer and Correlation with Postconceptional Age in Premature Infants

Catarina Monteiro,
Maria Vivas,
Júlio Almeida
et al.

Abstract: Purpose: This study aimed to determine a normative range of intraocular pressure (IOP) values measured with Icare rebound tonometer in premature infants and evaluate IOP variation over time and its correlation with the progression of postconceptional age (PCA). By doing so, we also evaluated advantages of this IOP-measuring method in this population when compared to more traditional methods. Methods: We conducted a single-center prospective study that included premature infants (gestational age ≤32 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…13 Other research teams did longitudinal studies of IOP in premature newborns to follow its changes with their maturation. 2,[16][17][18][19][20][21] All of the studies showed a statistically significant (p<0.01) decline of IOP values with a negative correlation between the postconceptual age and birth weight of the infants. Only Choo et al did not find a statistically significant difference in IOP between premature and full-term newborns.…”
Section: Screeningmentioning
confidence: 91%
“…13 Other research teams did longitudinal studies of IOP in premature newborns to follow its changes with their maturation. 2,[16][17][18][19][20][21] All of the studies showed a statistically significant (p<0.01) decline of IOP values with a negative correlation between the postconceptual age and birth weight of the infants. Only Choo et al did not find a statistically significant difference in IOP between premature and full-term newborns.…”
Section: Screeningmentioning
confidence: 91%